The genetic deletion of the Dual Specificity Phosphatase 3 (DUSP3) attenuates kidney damage and inflammation following ischaemia/reperfusion injury in mouse. (9th November 2021) - Khbouz, Badr; Rowart, Pascal; Poma, Laurence; Dahlke, Eileen; Bottner, Martina; Stokes, Matthew; Bolen, Géraldine; Rahmouni, Souad; Theilig, Franziska; Jouret, François
Abstract: Aim: Dual Specificity Phosphatase 3 (DUSP3) regulates the innate immune response, with a putative role in angiogenesis. Modulating inflammation and perfusion contributes to renal conditioning against ischaemia/reperfusion (I/R). We postulate that the functional loss of DUSP3 is associated with kidney resistance to I/R. Methods: Ten C57BL/6 male WT and Dusp3 −/− mice underwent right nephrectomy and left renal I/R (30 min/48 hours). Renal injury was assessed based on serum levels of urea (BUN) and Jablonski score. The expression of CD31 and VEGF vascular markers was quantified by RT‐qPCR and immuno‐staining. Renal resistivity index (RRI) was measured in vivo by Doppler ultrasound. Comparative phosphoproteomics was conducted using IMAC enrichment of phosphopeptides. Inflammatory markers were quantified at both mRNA and protein levels in ischaemic vs non‐ischaemic kidneys in WT vs Dusp3 −/− . Results: At baseline, we located DUSP3 in renal glomeruli and endothelial cells. CD31‐positive vascular network was significantly larger in Dusp3 −/− kidneys compared to WT, with a lower RRI in Dusp3 −/− mice. Following I/R, BUN and Jablonski score were significantly lower in Dusp3 −/− vs WT mice. Phosphoproteomics highlighted a down‐regulation of inflammatory pathways and up‐regulation of phospho‐sites involved in cell metabolism and VEGF‐related angiogenesis in Dusp3 −/− vs WT ischaemic kidneys. Dusp3 −/− ischaemic kidneys showed decreased mRNA levels of CD11b, TNF‐α, KIM‐1, IL‐6, IL‐1β and caspase‐3 compared to controls. The numbers of PCNA‐, F4‐80‐ and CD11b‐positive cells were reduced in Dusp3 −/− vs WT kidneys post ‐I/R. Conclusion: Genetic inactivation of Dusp3 is associated with kidney conditioning against I/R, possibly due to attenuated inflammation and improved perfusion.